Effects of Electromagnetic Acupuncture Combined with Integrative Korean Medicine Treatment on Pain and Dysfunction in a Patient with Knee Osteoarthritis: A Case Report - Jihun Kim; Taewook Lee; Sookwang An; Geun Hyeong An; Yoona Oh; Gi Young Yang (MEDrang Inc., 2024)
Knee osteoarthritis (KOA) is a prevalent degenerative joint disease causing significant pain and dysfunction. This case report presents the use of electromagnetic acupuncture utilizing a Whata 153 device generating a magnetic field to enhance acupuncture stimulation for the treatment of KOA. A 69-year-old female diagnosed with KOA experienced a reduction in pain (numerical rating scale score from 7 to 4), improved gait, and decreased stiffness and swelling after daily electromagnetic acupuncture treatments during hospitalization. In addition, the Korean Western Ontario and McMaster Universities Osteoarthritis Index scoreimproved from 20 to 14, and the patient rated her overall improvement as "significantly improved" on the patient's global impression of change scale. Although these findings suggest potential benefits of electromagnetic acupuncture for KOA, the case report design limits its generalizability. More controlled trials are warranted to confirm the efficacy and safety of electromagnetic acupuncture as a treatment of KOA.